Cheese Production and Export Supply Chain : Armenia - International Finance Corporation (Washington, DC, 2018)
The mapping of the production and export supply chain of cheese has been implemented within the framework of the International Finance Corporation’s (IFC) Armenia Investment Climate Reform Project, which is implemented by the Trade and Competitiveness Global Practice of the World Bank Group (WBG), in partnership with Austria’s Federal Ministry of Finance and Hungarian Partnership Funding/Hungary EXIM Bank, at the request of the Ministry of Economic Development and Investments and the Development Foundation of the Republic of Armenia.